2007
DOI: 10.1016/s1472-6483(10)60362-8
|View full text |Cite
|
Sign up to set email alerts
|

Proximal tubal disease: the place for tubal cannulation

Abstract: Tubal disease is the cause of subfertility in approximately 30% of women, and 10-25% of these are due to proximal tubal obstruction. False-positive diagnosis of proximal tubal obstruction can be as high as 50%. A decrease in expertise in tubal microsurgery has resulted largely from the use of IVF as the treatment option for most causes of infertility and more specifically for tubal factor infertility. Selective salpingography and tubal cannulation have a unique role in the management of tubal infertility and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 29 publications
0
21
0
Order By: Relevance
“…Tubal and uterine cavity diseases commonly compromise female fertility (14% of couples who require specialist treatment) [1]. In particular, uterine anomalies or structural abnormalities of the fallopian tubes are diagnosed in 3% and 16% infertile women, respectively [2].…”
Section: Introductionmentioning
confidence: 99%
“…Tubal and uterine cavity diseases commonly compromise female fertility (14% of couples who require specialist treatment) [1]. In particular, uterine anomalies or structural abnormalities of the fallopian tubes are diagnosed in 3% and 16% infertile women, respectively [2].…”
Section: Introductionmentioning
confidence: 99%
“…Infertility etiology is multifactorial, but in one-third of the cases it is caused by a female factor. Tubal pathology is a common cause of female infertility (14% of couples who require specialist treatment) [2]. Fallopian tubes are important for fertility because they transport gametes and embryos, allow the timely passage of the embryo to the uterus and have an essential role in its early development.…”
Section: Introductionmentioning
confidence: 99%
“…There is usually a poor correlation between hysterosalpingographic studies and falloposcopy since falloposcopy gives a more accurate visual status of the tube and with HSG false positives could be as high as 40%. [8][9][10] Eight infertility patients with proximal tubal block by hysterosalpingograph had falloposcopy and patency was established in 9 out of 12 tubes, falloposcopy revealed five tubes with multiple or extensive intratubal lesions that would be unsuitable for unilocular tubal resection with subsequent reanastomosis and recanalization for which five tubes had only minor pathologies, two of which became pregnant and only 2% of the tubes needed tubal surgery. Another randomized controlled study revealed that there is a significant benefit in pregnancy rate when tubes were flushed with oil soluble media and this was supported by falloposcopic procedures.…”
Section: Results From Falloposcopymentioning
confidence: 99%
“…Another randomized controlled study revealed that there is a significant benefit in pregnancy rate when tubes were flushed with oil soluble media and this was supported by falloposcopic procedures. [10][11][12][13] Schille et al revealed in his studies that proximal tubal blockage which is a major cause of subfertility in women could be easily managed with falloposcopy and this yielded good pregnancy outcome. 14 Further studies revealed the importance of falloposcopy in performing tubal cannulation under laparoscopic guidance with both the coaxial and LEC falloposcopes and they achieved 80% success rate.…”
Section: Results From Falloposcopymentioning
confidence: 99%
See 1 more Smart Citation